Hybrid solar trough and solar cell system I - Cheng, Lee Hong. (2010)
The solar trough and solar cell with tracking system is served the purpose of converting clean energy into electricity at higher efficiency utilizing the concept of focused light beam. The system consisted of solar cell, reflector and trough, and the tracking system.